1994
DOI: 10.1177/088391159400900303
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modifications of Heparin.1: Reaction of Partially N-Desulfated Heparin with Glutaraldehyde

Abstract: Purified glutaraldehyde was allowed to react with the primary amino groups generated by mild acidolysis of glucosamine N -sulfamino residues present in heparinic acid. The reaction yielded high molecular mass heparinoids (HMMHEP) or hydrogels, depending on experimental conditions. It was shown that a selected HMMHEP exhibited a higher anticoagulant activity than the starting heparin or the parent partially N -desulfated heparin. This HMMHEP degraded slowly in vitro in an aqueous medium buffered at pH = 7.4. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Partially de‐ N ‐sulfated heparins have been exploited to generate imines with dialdehydes such as glutaraldehyde or with long‐chain aldehydes such as dodecanal . The resulting conjugates were screened for their anticoagulant activity.…”
Section: Heparin and Heparan Sulfatementioning
confidence: 99%
“…Partially de‐ N ‐sulfated heparins have been exploited to generate imines with dialdehydes such as glutaraldehyde or with long‐chain aldehydes such as dodecanal . The resulting conjugates were screened for their anticoagulant activity.…”
Section: Heparin and Heparan Sulfatementioning
confidence: 99%
“…However, some reports focus on the preparation of selectively N-desulfated heparin [119, 129] which could be used for mechanistic studies of protein interactions and molecular delivery, because N-desulfated heparin/HS loses a large portion of its anticoagulant activity (3–5 times less than regular heparin) [130]. Crosslinking of N-desulfated heparin with glutaraldehyde under formation of high molar mass polymers or hydrogels was reported as well [131]. …”
Section: Structural Modification Of Gags For Development Into Drug mentioning
confidence: 99%
“…Indeed, it has been previously shown that heparin retained its anticoagulant activity even after drastic chemical modifications as long as these modifications did not involve N‐desulfatation. 20…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been previously shown that heparin retained its anticoagulant activity even after drastic chemical modifications as long as these modifications did not involve N-desulfatation. 20 Antifactor Xa activity. Heparin activity was assessed by measuring antifactor Xa activity according to USP 28 monography.…”
Section: Surface Characterizationmentioning
confidence: 99%